Game Edukasi Jenis Bunga Berbasis Android - Taqwa, Laksamana; Sarudin, Sarudin; Sundari, Siti (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2025)
Android-based educational games are increasingly evolving as interactive learning tools. This research aims to design and develop an educational game that introduces various types of roses. The game is developed using Unity and the C# programming language, following the MDLC (Multimedia Development Life Cycle) method, which includes planning, data collection, implementation, and testing stages. The main features of this game include introducing different rose species along with their Latin names and characteristics, as well as interactive games such as quizzes and puzzles to enhance user engagement. Testing was conducted using the black-box method to ensure the game's functionality. Evaluations based on questionnaires indicate that this game is highly effective in improving users' knowledge of rose species. The results of this study are expected to contribute to the development of more engaging and educational technology-based learning media.